Regulation of M-2, M-3, and M-4 muscarinic receptor expression in K562 chronic myelogenous leukemic cells by carbachol - AYDIN OMAY, BANU; CABADAK, HÜLYA (INFORMA HEALTHCARE, 2011)
Context: Muscarinic receptors mediate a variety of cellular responses to acetylcholine, including inhibition of adenylate cyclase, breakdown of phosphoinositide and modulation of ion channels. These receptors are relatively abundant in the central nervous system and peripheral parasympathetic nervous system. Many cells express a mixture of muscarinic receptor transcripts. Changes in muscarinic M-2 and M-3 receptor mRNA levels in response to agonist treatment have been reported in cerebellar granule cells, Chinese hamster ovary cells, lymphocytes and in the human neuroblastoma cell line SH-SY5Y. Objective: In this study, we investigated the effects of agonist stimulation on cell proliferation and on the levels of muscarinic receptor expression in K562 chronic myelogenous leukemia cells. Methods:Total RNA and crude membrane fractions were prepared from K562 cells challenged with carbachol (CCh). Muscarinic receptor subtype expression was determined by RT-PCR and western blot analysis. Proliferation and cell viability were evaluated by the trypan blue exclusion test and BrDU labeling. Results: We showed that CCh-treatment leads to changes in muscarinic M-2, M-3, and M-4 receptor transcripts as well as M-2 and M-3 protein levels. We also found that CCh decreased proliferation of K562 cells in a time dependent manner, an effect prevented by atropine. These results suggest that CCh modulates K562 chronic myelogenous leukemic cells proliferation through muscarinic acetylcholine receptors.
Keywords: Agonist; cell proliferation; mRNA regulation; INDUCED DOWN-REGULATION; CEREBELLAR GRANULE CELLS; MESSENGER-RNA EXPRESSION; ACETYLCHOLINE-RECEPTOR; CHOLINERGIC SYSTEM; DNA-SYNTHESIS; SUBTYPES; LINE; ACTIVATION; IDENTIFICATION